CYTOKINE GENES AS GENETIC MARKERS OF CONTROLLED AND UNCONTROLLED ATOPIC BRONCHIAL ASTHMA - M. Smolnikova V.; M. Freidin B.; S. Smirnova V.; М. Смольникова В.; М. Фрейдин Б.; С. Смирнова В. (Medical Immunology (Russia), 2017)
Atopic bronchial asthma (ABA) is a multifactorial disease; its development is dependent on many environmental and genetic factors. Genetic risk factors can affect the clinical phenotype of ABA and the level of therapeutic control over the disease. Cytokine genes are crucially important in pathogenesis of ABA as they encode proteins participating in immune response and development of inflammation in bronchi. It was suggested that the therapeutic control of the disease is genetically mediated and depends on the presence of one or another allele in genes of mediators, participating in ABA pathogenesis. The knowledge about genetic markers will allow to predict clinical course of ABA in children. We carried out the analysis of association between genes of pro- and anti-inflammatory cytokines with the level of therapeutic control of ABA. In children with controlled and uncontrolled ABA (CABA and UABA, respectively; n = 110), and in general a population sample (n = 138), we analysed 11 polymorphisms: IL2 (rs2069762), IL4 (rs2070874 и rs2243250), IL5 (rs2069812), IL10 (rs1800872 and rs1800896), IL12B (rs3212227), TNFA (rs1800629 and rs1800630), TGFB1 (rs1800469), and IFNG (rs2069705), encoding cytokines actively participating at the development of allergic inflammation. According to results of present study, the prevalence of alleles and genotypes of the analysed loci in the East Siberia Caucasians is consistent with the data in other world Caucasian populations. We have found statistically significant differences between UABA and control groups for the prevalence of IL2 (rs2069762) polymorphism: GG genotype was more common in control group (14.1% compared to 5.9%, р = 0.03). It was shown that the IL2*T allele and ТТ genotype of the rs2069762 are associated with the increased risk of uncontrolled ABA. A comparison of the haplotypes of IL4 (rs2070874 and rs2243250) gene with correction for sex and age within an additive model revealed that the most common haplotype СC (prevalence in ABA/CABA/UABA groups is 0.75/0.76/0.74, respectively) is protective against the development of ABA (RR 0.53±0.32; p = 0.044). A comparative analysis of TNFA (rs1800629 and rs1800630) haplotypes has shown the GC haplotype to be protective against the risk of ABA (RR 0.59±0.17; р = 0.003) while the GA haplotype is positively associated with the disease (RR 2.07±0.25; р = 0.003). This was true for BA, regardless of the control over the disease (CABA GA: RR 1.93±1.2; p = 0.041; UABA GA: RR 2.43±0.31; p = 0.005). Thus, it was established that the studied cytokine genes are important for the development of ABA in children. These data were obtained for the first time for Caucasians of East Siberia. They are of interest in terms of accumulation of the data about the impact of cytokine genes polymorphism upon development of ABA and its therapeutic control in children. Атопическая бронхиальная астма (АБА) является многофакторным заболеванием и ее развитие зависит как от множества факторов окружающей среды, так и генетической компоненты. Генетические факторы риска развития АБА могут влиять на фенотип заболевания и степень контроля его течения. Существенный вклад в патогенез АБА вносят гены цитокинов, участвующие в иммунном ответе, развитии и активации воспаления дыхательных путей. Предполагается, что степень контроля заболевания является генно-опосредованным процессом и во многом зависит от наличия того или иного аллельного варианта в генах медиаторов, участвующих в патогенезе АБА. Знания о генетических маркерах позволит прогнозировать течение атопической бронхиальной астмы у детей. Исследование проведено для оценки ассоциации генов провоспалительных и противовоспалительных цитокинов с уровнем контроля течения атопической бронхиальной астмы (АБА). У больных детей с контролируемым (КАБА) и неконтролируемым (НАБА) течением заболевания (n = 110), а также в популяционной выборке (n = 138) изучены 11 полиморфизмов генов IL2 (rs2069762), IL4 (rs2070874 и rs2243250), IL5 (rs2069812), IL10 (rs1800872 и rs1800896), IL12B (rs3212227), TNFA (rs1800629 и rs1800630), TGFB1 (rs1800469), IFNG (rs2069705), кодирующих цитокины, принимающие активное участие в развитии и регуляции аллергического воспаления. По данным проведенного исследования, у европеоидов Восточной Сибири частоты аллелей и генотипов по изученным полиморфизмам соответствуют таковым в других европеоидных популяциях мира. Получены статистически значимые отличия между группой НАБА и контрольной выборкой по частотам генотипов IL2 (rs2069762): генотип GG чаще встречается в контрольной группе (14,1% по сравнению с 5,9% в группе НАБА, р = 0,03). Показано, что аллель IL2*T или генотип ТТ (rs2069762) предрасполагает к развитию неконтролируемого течения АБА. При сравнении гаплотипов IL4 (rs2070874 и rs2243250) с поправкой на пол и возраст, с использованием аддитивной модели наследования, показано, что наиболее часто встречающийся гаплотип СC (частота в группах АБА/КАБА/НАБА составляет 0,75/0,76/0,74 соответственно) является протективным в отношении риска развития атопической бронхиальной астмы (RR 0,53; SE 0,32; p = 0,0439). Сравнительный анализ гаплотипов TNFA (rs1800629 и rs1800630) с поправкой на пол и возраст, с использованием аддитивной модели наследования, показал, что гаплотип GC является протективным в отношении риска развития АБА (RR 0,59±0,17; р = 0,0028), а гаплотип GA – предрасполагающим к заболеванию (RR 2,07±0,25; р = 0,0034). Это характерно для атопической бронхиальной астмы вне зависимости от степени контроля заболевания (КАБА GA: RR 1,93±1,2; p = 0,0414; НАБА GA: RR 2,43±0,31; p = 0,0051). Установлено, что гены цитокинов вносят вклад в развитие АБА у детей. Эти данные для европеоидной популяции Восточной Сибири получены впервые и представляют интерес с точки зрения пополнения данных о вкладе полиморфизма генов цитокинов в развитие атопической бронхиальной астмы и контроля течения заболевания у детей.